Optimization of Fibrin Glue Spray Systems for Ophthalmic Surgery - Chaurasia, Shyam S. (The Association for Research in Vision and Ophthalmology, 2012)
PURPOSE: To optimize fibrin glue (FG) spray for ophthalmic surgery using two spray applicators, EasySpray and DuploSpray systems, by varying the distance from point of application and the pressure/flow rate, and to compare the adhesive strength of sutured and sutureless (FG sprayed) conjunctival graft surgery in a rabbit model. METHODS: FG was sprayed on a 0.2 mm-thick sheet of paper using EasySpray by variously combining application distances of 2.5, 5, 7.5, and 10 cm with pressures of 10, 15, and 20 psi. DuploSpray was used at the same distances but with varying flow rates of 1 and 2 L/min. Subsequently, FG was sprayed on porcine corneas and FG thickness was analyzed by histology. In addition, adhesive strength of the conjunctival graft (0.5 × 0.5 cm) attached to the rabbit cornea by sutured and sutureless surgery (FG spray) was compared using a tension meter. RESULTS: Histology measurements revealed that the FG thickness decreased with increases in distance and pressure of spray using the EasySpray applicator on paper and porcine corneal sections. The adhesive strength of the sutured conjunctival graft (41 ± 4.85 [kilopascal] KPa) was found to be higher than the graft attached by spraying (10 ± 2.3 KPa) and the sequential addition of FG (6 ± 0.714 KPa). CONCLUSIONS: The EasySpray applicator formed a uniform spread of FG at a distance-pressure combination of 5 cm and 20 psi. The conjunctival graft attached with sutures had higher adhesive strength compared with grafts glued with a spray applicator. Although the adhesive strength of FG applied through the applicator was similar to the drop-wise sequential technique, the former was more cost effective because more samples could be sprayed compared with the sequential manual technique. TRANSLATIONAL RELEVANCE: The standardization of the spray system for the application of FG in ophthalmology will provide an economical method for delivering consistent healing results after surgery.